The weight of ink ebook - Kadish, Rachel (2017)
WINNER OF A NATIONAL JEWISH BOOK AWARD A USA TODAY BESTSELLER "A gifted writer, astonishingly adept at nuance, narration, and the politics of passion."—Toni Morrison Set in London of the 1660s and of the early twenty-first century, The Weight of Ink is the interwoven tale of two women of remarkable intellect: Ester Velasquez, an emigrant from Amsterdam who is permitted to scribe for a blind rabbi, just before the plague hits the city; and Helen Watt, an ailing historian with a love of Jewish history. When Helen is summoned by a former student to view a cache of newly discovered seventeenth-century Jewish documents, she enlists the help of Aaron Levy, an American graduate student as impatient as he is charming, and embarks on one last project: to determine the identity of the documents' scribe, the elusive "Aleph." Electrifying and ambitious, The Weight of Ink is about women separated by centuries—and the choices and sacrifices they must make in order to reconcile the life of the heart and mind.